The lost duke of Wyndham - Quinn, Julia (New York : Avon, 2008)
Highwayman Jack Audley has never wanted to be responsible for an ancient heritage and the livelihood of others. But when he is recognized as the long-lost son of the House of Wyndham, his carefree life is over. If his birth proves to be legitimate, Jack will find himself with the one title he has never wanted: Duke of Wyndham. Grace Eversleigh has spent the last five years toiling as the companion to the dowager Duchess of Wyndham. It is a thankless job, with very little break from the routine... until Jack Audley lands in her life.
Keywords: Brigands and robbers -- Fiction; Inheritance and succession -- Fiction